Potential Toxic Metal Concentration and Risk Assessment in Agricultural Soil and Lentil Crop (Lens culinaris Medik) in Dawunt Woreda, Northwest Wollo, Ethiopia - Baynesagn Biyazen Belay; Asamene Embiale Taye (Journal of Toxicology)
Health implications for the population due to consuming contaminated crops have been a great concern worldwide. This study aimed to measure the levels of potential toxic elements in lentils and their growing soil in Dawunt Woreda, Ethiopia. Accordingly, 15 soil samples along with the lentil samples were collected to measure the level of potential toxic elements, including chromium (Cr), manganese (Mn), iron (Fe), lead (Pb), cadmium (Cd), copper (Cu), and cobalt (Co), by using an inductively coupled plasma optical emission spectrometer and for assessing the potential ecological and human health risk. The wet digestion method using aqua regia (HCl/HNO3 3 : 1) was employed for soil and lentil sample preparation. The mean concentrations of Fe, Mn, Co, Cu, Cd, Pb, and Cr in the lentil sample were 60.4, 9.68, 0.75, 5.7, 0.25, 0.9, and 1.15 mg/kg, respectively. In soil, the mean concentrations of Fe, Mn, Co, Cu, Cd, Pb, and Cr were 649, 19.9, 3.32, 40.0, 15.2, 1.83, and 69.1 mg/kg, respectively. All of the potential toxic metals in agricultural soil and lentil samples were found to be below the reference level set by the World Health Organization, except Cd, in the soil samples. Five single metal and three cumulative pollution index parameters were employed for the data and results showed that Fe, Cu, and Cr moderately pollute the soil and are highly contaminated by Cd. The cumulative pollution indices also confirmed that the extent of soil pollution varied from highly contaminated to moderate contamination. The possible health risks at various exposure routes have also been estimated. The single-metal and cumulative-metals health risks (cancer and noncancer) of adults and children due to chronic exposure to soil and consumption of lentils were estimated using the health quotient and health index values as per the United States Environmental Protection Agency guidelines. Thus, the results revealed no significant adverse health risks (cancer and noncancer) for adults and children. Therefore, the inhabitants in the study area have no significant health impacts due to either the consumption of lentil crops or exposure to agricultural soil particles.